2021
DOI: 10.3389/fmicb.2021.766878
|View full text |Cite
|
Sign up to set email alerts
|

Yeast β-Glucan Altered Intestinal Microbiome and Metabolome in Older Hens

Abstract: The prebiotics- and probiotics-mediated positive modulation of the gut microbiota composition is considered a useful approach to improve gut health and food safety in chickens. This study explored the effects of yeast β-glucan (YG) supplementation on intestinal microbiome and metabolites profiles as well as mucosal immunity in older hens. A total of 256 43-week-old hens were randomly assigned to two treatments, with 0 and 200 mg/kg of YG. Results revealed YG-induced downregulation of toll-like receptors (TLRs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 95 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…29 Furthermore, yeast β-glucan induces the downregulation of Il-6 and Tnf-α and upregulation of Ocln and modulates the abundance of Lactobacillales and Enterobacteriales at the order level in chickens. 30 Taken together, the combined effects of A4 + S have the potential to mitigate colitis through the enhancement of the immune system and gut barrier, as well as the modification of the gut microbiota. This phenomenon may be attributed to the comparatively higher concentration of β-glucan in Km A4 compared to Sb MYA-796.…”
Section: Food and Function Papermentioning
confidence: 99%
“…29 Furthermore, yeast β-glucan induces the downregulation of Il-6 and Tnf-α and upregulation of Ocln and modulates the abundance of Lactobacillales and Enterobacteriales at the order level in chickens. 30 Taken together, the combined effects of A4 + S have the potential to mitigate colitis through the enhancement of the immune system and gut barrier, as well as the modification of the gut microbiota. This phenomenon may be attributed to the comparatively higher concentration of β-glucan in Km A4 compared to Sb MYA-796.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Numerous other studies have also demonstrated anticancer effects of S. cerevisiae β-glucan ( Sambrani et al, 2021 ) including prevention of DNA damage in CHO cells ( Oliveira et al, 2007 ), induced proliferation and activation of peripheral blood monocytes in patients with advanced breast cancer ( Demir et al, 2007 ) and a variety of other immunostimulatory effects on various cell lines ( Yoon et al, 2008 ) and in vivo ( Mo et al, 2017 ). S. cerevisiae β-glucans have also been reported as antidiabetic agents through their effects on blood glucose levels and insulin resistance ( Cao et al, 2017 ), as potential prebiotic compounds by altering gut microbiome and metabolite profiles ( Zhen et al, 2021 ; Wang et al, 2020 ), and finally as capable of reducing blood cholesterol levels and promoting wound healing ( Borchani et al, 2016 ).…”
Section: Relationship Between Cell Wall Biochemical Composition and S...mentioning
confidence: 99%
“…Intestinal bacteria can eliminate pathogens by releasing ligands, such as microbial-related molecular patterns that bind to host cell receptors, to stimulate the immune system (Brisbin et al, 2008), and can also produce antimicrobial peptides to prevent pathogen colonization (Mancabelli et al, 2016). Intestinal microbes produce a variety of bioactive substances and metabolites, such as lipopolysaccharide, peptidoglycan, DNA and extracellular vesicles, short-chain fatty acids (SCFAs), polyamines, secondary bile acids, vitamins, neurotransmitters and phenolic compounds (Zhen et al, 2021;Wang Q. et al, 2023). They can directly or indirectly participate in a variety of physiological processes in health and disease, including host development, metabolism, immune regulation, and intercellular signal communication (Nicholson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%